Implementation of Maqashid Syari'ah Values in The Islamic Education Curriculum - Katni Katni; Sarnawati Sarnawati; Nabilla Azzahwa; Hardanenggar Kusumaningtyas; Sheylla Oktavia Syahri Ramadhani; Helmy Yahya (CV. Bimbingan Belajar Assyfa, 2025)
Maqashid Syari'ah in the perspective of Islamic education refers to efforts to direct the entire process and objectives of Islamic education to achieve the welfare of humanity, both in this world and the hereafter, in accordance with the basic principles of Islamic law. This concept transforms the broader objectives of Islamic law into the framework of Islamic education. This research was conducted through a mini-research (research library) using a literature review method as data collection in the research. Therefore, this article aims to explain the maqashid syari'ah from the perspective of Islamic education. The development of globalization has an impact on various aspects of human life. The main objectives of Islamic law (maqashid syari'ah) are very necessary in the context of practical solutions to problems in the world of Islamic education that were not found in the time of the Prophet, the companions, or the period of the tabi'in. Maqashid syari'ah is an important aspect of the world of Islamic education. This also answers that Islamic law can keep up with the times. However, the legal basis remains based on a solid legal foundation, namely the Qur'an and the had.